PERANCANGAN WEBSITE KATALOG SEBAGAI MEDIA PEMASARAN DI MAJALENGKA CREATIVE CENTER - Yanuari, Puri Dewi; Sujadi , Harun (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
Majalengka Creative Center (MCC) is a creative industry hub in Majalengka Regency that still faces marketing limitations due to its reliance on offline sales. This study aims to design and implement a catalog website as a marketing medium using the Waterfall method, which includes requirement analysis, system design with UML, implementation with PHP and MySQL, and testing with blackbox methods. The developed website provides product management features for administrators and catalog browsing, product search, and ordering via WhatsApp for users. Testing results show that all features function as expected, enabling the system to improve information management efficiency, expand market reach, and provide consumers with a more practical shopping experience.